2011
DOI: 10.1111/j.1442-2042.2010.02697.x
|View full text |Cite
|
Sign up to set email alerts
|

Voiding dynamics in women with stress urinary incontinence and high‐stage cystocele

Abstract: Objectives:The aim of this study was to identify the urodynamic features of women with stress urinary incontinence (SUI) or with high-stage (stage 3 or greater) cystocele (HSC) as compared with symptom-free women. Methods: Fifty-six neurologically intact women with SUI and 47 women with HSC but without SUI were prospectively evaluated. All patients underwent full urodynamics, in addition to basic clinical evaluations. The urodynamic parameters of SUI and HSC were compared to the ones obtained from 78 urologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Contractility indices such as W max and BCI seem to be influenced by the degree of outlet resistance both in males and females . Thus, it could be argued that abnormal post‐void residuals should be attributed to detrusor insufficiency after BOO has been excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contractility indices such as W max and BCI seem to be influenced by the degree of outlet resistance both in males and females . Thus, it could be argued that abnormal post‐void residuals should be attributed to detrusor insufficiency after BOO has been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it could be argued that abnormal post‐void residuals should be attributed to detrusor insufficiency after BOO has been excluded. Unfortunately, there is no definitive urodynamic definition for female outflow obstruction . The limited articles proposing the use of p detQmax and Q max from PFS to define BOO have used quite different cut‐off values, as mentioned above …”
Section: Discussionmentioning
confidence: 99%
“…where V t = volume of noncontracting bladder wall tissue [7]. Although some studies report WF and WF max , no consensus has been made regarding normative values particularly in female patients [6,8,9]. A WF max of <12 μW/mm 2 for males and <5 μW/mm 2 for postmenopausal females has been used in some studies to define detrusor underactivity [8,10,11].…”
Section: Assessment Of Bladder Contractilitymentioning
confidence: 98%
“…It is suggested that a Pdet.qmax >20–25 cmH 2 O and Qmax <12–15 mL/s warrants the diagnosis of female BOO 67 . Recently, in some of the literature about PFS for POP, nomograms for BPO or BCI in men have been used to analyze PFS parameters for women 68,69 . However, BCI might largely overestimate Pdet.iso in female patients 24 .…”
Section: Pfs In Male Boomentioning
confidence: 99%
“…67 Recently, in some of the literature about PFS for POP, nomograms for BPO or BCI in men have been used to analyze PFS parameters for women. 68,69 However, BCI might largely overestimate Pdet.iso in female patients. 24 It is urgently necessary to investigate whether nomograms or indicators for male BOO can be applied to female patients.…”
Section: Pfs In Female Boomentioning
confidence: 99%